Impact of type II diabetes on LV remodeling and function in patient with severe aortic stenosis. (4th February 2022) - Seillier, G; Pozzi, M; Paillard, M; Pierrard, R; Chalabreysse, L; Nouviant, C; De-Bourguignon, C; Givre, L; Farha, F; Vola, M; Uhlrich, W; Bessyre-Des-Horts, T; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): PHRC inter régional Background: Type II diabetes (T2DM) can specifically cause left ventricular (LV) remodeling and systolic and/or diastolic abnormalities. This diabetic cardiomyopathy is associated with an increased risk of heart failure. T2DM is frequently associated with LV pressure overload as encountered in aortic stenosis (AS). The effect of T2DM on LV remodeling induced by AS remained unclear. Purpose: We aimed to evaluate the impact of T2DM on left ventricular (LV) remodeling and function in patients with severe AS referred for aortic valve replacement. Methods: We included patients with severe AS and no overt heart disease referred for aortic valve replacement. Patients with atrial fibrillation, left ventricular ejection fraction (LVEF) <50%, significant coronary stenosis or a more than mild associated valvular heart disease were excluded. Baseline ultrasound parameters were measured including 2D and 3D left ventricle mass (LVM), LVEF, posterior wall thickness (PWT) and global longitudinal strain (GLS). We also studied LV diastolic function and left ventricular filling pressure according to current guidelines. Results: 82 patients were included; 32 were diabetics. Hypertension and dyslipidemia were more frequent in T2DM patients. Aortic mean gradient, aortic valve area and cardiac index were similar between the two groups. There was no difference in valvuloarterial impedance indexed to height^2.04. PWT, 3D LVM and 3D LVM index to height^2.7 were higher in T2DM patients (p = 0.03, p = 0.01 and p = 0.04, respectively). In multivariable analysis, after controlling for age, gender, BMI and hypertension, T2DM remained associated with a greater 3D LVM index (p= 0.04). Diabetic patients also presented a worse LV systolic function with a lower absolute value of GLS compared to non-diabetics (15.1 ± 2.7 vs. 17.8 ± 2.0; p < 0.01). The association of T2DM with a decreased GLS remained significant in multivariate analysis (p < 0.01; Table 1). Estimated left ventricular filling pressure was not significantly affected by T2DM. However, there was a trend towards more patients with elevated LV filling pressure in T2DM group (40% vs 22% in non T2DM patients; p = 0.08). Conclusion: T2DM increases LV hypertrophy and LV dysfunction in patients with severe AS.  Prognostic issues should be further assessed as it may encourage an earlier management of T2DM patients with severe AS.